KUALITAS PELAYANAN ONLINE “PENDAFTARAN MANDIRI AKTA TANAH (PERMATA)” DI KANTOR PERTANAHAN KOTA SEMARANG (Studi Kasus Pelayanan Balik Nama Sertifikat Hak Atas Tanah - Ikha Nathalia Puspitasari; Nina Widowati (Journal of Public Policy and Management Review, 2019)
Service quality is the assessment of services from recipients of public services to the organizer, so that in the form of administration, services or goods can satisfy the community. The demands of service recipients and supported by technological sophistication encourage the government to provide services based online. One of the government agencies that implemented it was the Semarang City Land Office, through online services "Independent Registration of Land Deeds". PERMATA online service to facilitate PPAT (Land Deed Making Officials) in Semarang City working area in order to improve data maintenance, so that it will be easier, simpler and faster to implement, because it is integrated online with the KKP Web application. The research objective was to analyze and describe the quality of PERMATA's online services at the Semarang City Land Office (Case Study of Service Behind the Name of the Right to Land Certificate) as well as what were the inhibiting factors of service quality. This study uses a qualitative descriptive research method. The results of the research on PERMATA's online service quality are not as expected, seeing the 5 dimensions of tangible, reliability, responsiveness, assurance and empathy that: a) There are infrastructure facilities that have not been fulfilled; b) Poor reliability of employees aged 50 years and over; c) Service efforts that have not been in accordance with procedures; d) Response of employees to low applicants when providing services; e) The absence of complaints media services online and; f) Does not provide a guarantee of completing service. The inhibiting factor of the quality of online services PERMATA is the PPAT Staff rule factor that is not disciplined in queuing and organizational factors related to the unequal division of labor systems. Therefore the need to improve the quality and quantity for employees and enforce the rules according to what has been made. Then procuring adequate infrastructure to support service quality.